2020
DOI: 10.1016/j.compag.2020.105734
|View full text |Cite
|
Sign up to set email alerts
|

Online milk composition analysis with an on-farm near-infrared sensor

Abstract: On-farm monitoring of milk composition can support close control of the udder and metabolic health of individual dairy cows. In previous studies, near-infrared (NIR) spectroscopy applied to milk analysis has proven useful for predicting the main components of raw milk (fat, protein, and lactose). In this contribution, we present and evaluate a precise tool for online milk composition analysis on the farm. For each milking, the online analyzer automatically collects and analyses a representative milk sample. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
(25 reference statements)
4
23
0
Order By: Relevance
“…The prediction ability of NIRS instruments on non-homogenized milk has been supported by recent studies [103,104]. Results indicated that NIRS may be used to determine milk quality in real-time during milking by providing information to farmers on milk characteristics and on physiological conditions of every cow [99,100].…”
Section: On-line Analysis Of Milk Quality (Total and Individual) In Tmentioning
confidence: 78%
See 2 more Smart Citations
“…The prediction ability of NIRS instruments on non-homogenized milk has been supported by recent studies [103,104]. Results indicated that NIRS may be used to determine milk quality in real-time during milking by providing information to farmers on milk characteristics and on physiological conditions of every cow [99,100].…”
Section: On-line Analysis Of Milk Quality (Total and Individual) In Tmentioning
confidence: 78%
“…However, most of the research was carried out on milk in off-line mode or rather not directly in the milking parlor. Recently, tests have been carried out using NIRS directly in the milking parlors to have individual check of each animal and to obtain information on milk quality and health status of the cows [8,93,[99][100][101][102][103][104]. Pioneering studies on the possibility of using NIRS instruments on farm were carried out by Tsenkova et al [87].…”
Section: On-line Analysis Of Milk Quality (Total and Individual) In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the off-line milk analyzers based on FTIR spectrometers working in the MIR spectral region, NIR technology allows developing portable devices for fast on-farm milk quality control [95] and analytical solutions for in-line applications in milking robots [96] and automated milking systems [97]. Authors claim that such devices can determine the concentrations of three major milk constituents (fat, protein, and lactose) and somatic cells count with accuracy which is quite acceptable for practical use.…”
Section: Near-infrared (Nir) and Visible Spectroscopymentioning
confidence: 99%
“…Advances in imaging, automation, sensors, electronic data exchange through "the cloud, " and data analytics offer extensive opportunities for specific interventions best aligned with physiological state and external inputs, even for animals housed under comingled conditions. Robotic milking and in-line milk composition analysis, for example, offer repeated opportunities to assess the cow's productive state and health (Diaz-Olivares et al, 2020;Michie et al, 2020). Could these data also be harnessed to indicate the affective state of the cow?…”
mentioning
confidence: 99%